Nitrification is the primary source for NO in N‐saturated subtropical forest soils: Results from in situ15N labeling. (20th February 2020) - Kang, Ronghua; Yu, Longfei; Dörsch, Peter; Mulder, Jan
Abstract : Rationale: Acidic subtropical forest soils that receive high atmospheric nitrogen (N) deposition have been identified as important sources of nitric oxide (NO). The relative importance of major processes producing NO is unclear. Methods: To partition NO sources, we conducted an in situ tracing experiment with 15 NH4 NO3 and NH4 15 NO3 in well‐drained acid soils of an N‐saturated subtropical forest in Chongqing, southwest China. Results: In the 15 NH4 NO3 treatment, the 15 N signature of NO emitted from the foot of the hillslope (Lower site) was similar to that of the NH4 + pool, indicating predominant autotrophic nitrification for NO formation. In the NH4 15 NO3 treatment, the 15 N enrichment of NO was smaller than that of the NO3 − pool, suggesting minor contribution of denitrification to NO production (~15%). Conclusions: Nitrification is the main process responsible for NO emissions, even in monsoonal summers when soil water‐filled pore space values are relatively high.